Readiness for Multimodal Teaching: Exploring EFL Pre-Service Teachers' Visual Literacy Competence - Renol Aprico Siregar (Universitas Indo Global Mandiri, 2026)
The increasing prominence of visual media in education has required EFL teachers to develop visual literacy. However, in many EFL teacher education contexts, visual literacy remains insufficiently integrated into pedagogical training, resulting in a gap between multimodal demands and teachers’ instructional readiness. Limited attention has been paid to how pre-service EFL teachers understand and enact visual literacy within their teaching practices, particularly in under-researched contexts such as Indonesia. To fill this gap, this study aimed to investigate pre-service teachers’ perceptions and ability to include visual literacy in teaching. An exploratory mixed-methods design was employed, involving 100 pre-service EFL teachers from a university in South Sumatera, Indonesia. Qualitative data were collected through semi-structured interviews, while quantitative data were obtained using a 4-point Likert-scale questionnaire. Participants were purposively selected based on their engagement with visual media in learning contexts. Data were analyzed using thematic analysis and descriptive statistics. The qualitative results of the study indicated that participants acknowledged visual literacy as a critical-thinking activity for profoundly understanding the underlying meaning of visual media. Furthermore, various aspects of their experience have impacted participants’ abilities. The primary identified influences were the extent of experience interpreting pictures, practices, university culture, and resources. The aspects of university preparation, including assignments, pedagogy subjects, and models of lecturing, are factors in developing the pre-service teachers’ visual literacy ability. The results suggest that visual literacy development is not solely an individual cognitive skill but is shaped by structured pedagogical experiences within teacher education. This study contributes to the field by highlighting the need to move beyond conceptual awareness toward the systematic integration of visual literacy in EFL teacher education, particularly through curriculum design and pedagogical modelling that support its practical enactment. Keywords: Multimodality, new literacy, pictures, visual literacy